1995
DOI: 10.3382/ps.0740563
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Migrating Myoelectric Complexes by Cholecystokinin and Gastrin in the Gastrointestinal Tract of Chickens

Abstract: Several mammalian avian species, including the chicken, show migrating myoelectric complexes (MMC) both in unfed and fed states. In these species, postprandial hormones seem to modulate but not to disrupt the MMC. To gain more information in this modulatory role, we evaluated the role of cholecystokinin (CCK) vs gastrin on the regulation of intestinal motility in chickens. Birds were implanted with eight electrodes for electromyography in the stomach, duodenum, jejunum, and ileum. In feed-deprived animals, CCK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Contraction of chicken ileal strips is stimulated by CCK-8 acting predominantly via receptors on neurons . Administration of CCK influences the migrating myoelectric complexes that control intestinal motility in the chicken intestine in a manner similar to that of feeding (Martínez et al, 1995). Sulfated CCK-8 induces hyperactivity in the duodenum (Martinez et al, 1993b).…”
Section: Cholecystokinin (Cck)mentioning
confidence: 97%
“…Contraction of chicken ileal strips is stimulated by CCK-8 acting predominantly via receptors on neurons . Administration of CCK influences the migrating myoelectric complexes that control intestinal motility in the chicken intestine in a manner similar to that of feeding (Martínez et al, 1995). Sulfated CCK-8 induces hyperactivity in the duodenum (Martinez et al, 1993b).…”
Section: Cholecystokinin (Cck)mentioning
confidence: 97%
“…The detailed mechanisms of regulation of the MMC in chickens have not been reported yet, but it is known that the appearance of the MMC is modulated by some gut hormones such as CCK and gastrin. The difference in the motility of the GI tract in fed and fasted states is unclear at present in the case of the bird MMC (70, 71).…”
Section: Regulation Of Gastrointestinal Motility By Mlnmentioning
confidence: 99%
“…The morphology and function of the GI tract in birds are different from those in mammals in the following three aspects: (i) the crop in the middle of the esophagus stocks food, (ii) there are two distinct stomach structures, the proventriculus that secretes digestive enzymes for chemical digestion and the gizzard for mechanical digestion, and (iii) a pair of a long cecum and short colon/rectum. Electromyogram measurements showed that the MMC, consisting of three phases like the mammalian IMC, is also present in the GI tract of avian species including chickens ( Gallus gallus domesticus ) (70, 71). However, the MMC originates from the duodenum, not the stomach, and it appears in both fed and fasted states, being different from the mammalian IMC.…”
Section: Regulation Of Gastrointestinal Motility By Mlnmentioning
confidence: 99%
“…For example, intravenous injection of CCK suppresses food intake in chickens (Savory and Gentle, 1980). CCK also modulates intestinal motility (Martín et al, 1995;Martínez et al, 1995;Rodríguez-Sinovas et al, 1997) and biliary flow in the gallbladder of chickens (Duke et al, 1987). Furthermore, CCK stimulates amylase secretion from the pancreas in chickens and ducks (Satoh et al, 1994;Xiao and Cui, 2004).…”
Section: Introductionmentioning
confidence: 99%